The Impact of Coronavirus Disease-19 on Pregnancy Outcomes, A Case Series - Bilge Cetinkaya Demir; Ozge Albayrak; Kiper Aslan (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To investigate the impact of Corona Virus Disease 19 (COVID-19) infection on pregnancy outcomes. STUDY DESIGN: This retrospective study was conducted at a tertiary university hospital between the years of October 2020-October 2021. All the pregnant women with COVID-19 diagnoses were enrolled in the study during this period. Demographic parameters, a history of Favipiravir use, COVID-19 symptoms, treatment approaches, hospitalization, intensive care unit admission, and obstetric and neonatal outcomes were recorded. RESULTS: A total of 92 patients were enrolled in the study. The mean age was 30+5 years. Forty-seven of the patients were asymptomatic (51%). The most common symptoms were respectively; fatigue (37.8%), fever (27.6%), dyspnea (22%), cough (17.8%), headache (11%), anosmia (4.4%), hyperemesis (4.4%), diarrhea (2.2%). There were 20 patients (21.7%) who were hospitalized. Eight of these women (8.6%) required intensive care unit admission due to COVID pneumonia-related acute respiratory distress syndrome. Five of the patients treated in the intensive care unit died due to respiratory failure. Two patients had a miscarriage before the 20th week. There were four stillbirths. The gestational weeks at which fetal death occurred were 24, 26, 28, and 38 weeks of gestation. There were 19 patients with a history of favipiravir use. There was not any other congenital abnormality due to Favipiravir usage. CONCLUSION: Our study showed that COVID-19 disease has similar symptoms in pregnant women to non-pregnant women, according to the literature data. However, COVID-19 infection increases the rates of pregnancy complications and maternal mortality